Deep Cervical Muscle Exercise Versus Soft Tissue Mobilization In Non-Specific Neck Pain - Ni Komang Ayu Juni Antari; Made Hendra Satria Nugraha; I Made Niko Winaya; Putu Rama Adhityadharma (Jurnal Keterapian Fisik, 2021)
Background: Neck pain is a common health problem in the working population. When studied by the International Classification of Functioning, Disability and Health (ICF), the problems that arise in non-specific neck pain include: neck pain, limited joint motion, and decreased functional ability in carrying out daily activities. The aim of this study was to compare the effectiveness of combination ultrasound therapy (UST) and deep cervical muscle exercise (DCME) versus combination ultrasound therapy (UST) and soft tissue mobilization (STM) on non-specific neck pain. Methods: This research was experimental with a randomized pre-test and post-test control group design, in which the study participants were divided into two groups randomly. The study participants were 20 people who were divided into the control group (n = 10) who were given the combined intervention of UST and DCME while the treatment group (n = 10) were given the combined intervention of UST and STM. Therapeutic evaluation measurement tools include: pain scale in the form of numeric rating scale and neck disability in the form of neck disability index. The research was carried out in the independent physiotherapy practice in Denpasar and Badung. The intervention was given 3 times in 3 weeks. Results: The results showed a decrease in neck pain and disability in each intervention group (p <0.05). However, there were no significant differences when compared between groups. Conclusion: Based on these results, it can be concluded that the combination of UST and DCME has the same results as the combination of UST and STM in reducing neck pain and disability in non-specific neck pain.